BUDAYA “NYETRUM” DALAM MEMPERTAHANKAN EKONOMI MASYARAKAT MENDAWAI SEBERANG PANGKALAN BUN - Jirhanuddin Jirhanuddin; Jelita Jelita; Ahmad Habibie (AL-QARDH, 2016)
Electric shock activity is an activity of an electric discharge into the water to look for fish using a stun. This activity is a way to sustain the local economy of the challenges existing conditions. Because of some reasons such as easy, effective and efficient this way is still used. Another reason this way is still used is because of economic necessity, small capital, and another effort is difficult to do.Even in preserving the environment, the Local Government who has authority in this case issued a regional regulation. Moving on from these problems, the writer wants to know the important role of the Electric shock activity at RT 01 Mendawai Seberang as the foundation to sustain the local economy as well as its impact, with the problem of the studies are (1) How does the Electric shock activity at RT 01 Mendawai Seberang Pangkalan Bun? (2) How is the role of culture in Electric shock activity on maintaining the local economy at RT 01 Mendawai Seberang Pangkalan Bun? (3)What is the impact of Electric shock activity for ecosystems and humans? This research is using qualitative descriptive approach. The subjects of this research are people who live in RT 01 Mendawai as the fisherman who use stun to look for fish. The object of this research is the culture of Electric shock activity in maintaining the local economy RT 01 Mendawai Seberang Pangkalan Bun. The techniques used in data collection are observation, interview and documentation. In the technical validity of the data, the researcher was used a triangulation process.             The results from the culture of electric shockonmaintaining economic society at the RT. 01 Mendawai Seberang Pangkalan Bunis an activity that has long been done and the result of cultural transformation that has been handed ancestors.This activity is one way to sustain the local economy of the challenges existing conditions. Using a stun for fishing has several factors because it is easy, effective and efficient.Economicnecessity, the capital required is not too large, another effort is difficult to do, and the domicile is the reason behind this culture is still being conducted until today. The impact of electric shock toward the ecosystem of fish just a little bit because it is not spent the ecosystem of fish. Only a small portion is taken for the purposes of trade. Whereas the impact on the fishermanthemselves the possibility exists, if its application is not appropriate and not in accordance with the existing procedures could harm the fishermanthemselves.Electric shock activity is an activity of an electric discharge into the water to look for fish using a stun. This activity is a way to sustain the local economy of the challenges existing conditions. Because of some reasons such as easy, effective and efficient this way is still used. Another reason this way is still used is because of economic necessity, small capital, and another effort is difficult to do.Even in preserving the environment, the Local Government who has authority in this case issued a regional regulation. Moving on from these problems, the writer wants to know the important role of the Electric shock activity at RT 01 Mendawai Seberang as the foundation to sustain the local economy as well as its impact, with the problem of the studies are (1) How does the Electric shock activity at RT 01 Mendawai Seberang Pangkalan Bun? (2) How is the role of culture in Electric shock activity on maintaining the local economy at RT 01 Mendawai Seberang Pangkalan Bun? (3)What is the impact of Electric shock activity for ecosystems and humans?                This research is using qualitative descriptive approach. The subjects of this research are people who live in RT 01 Mendawai as the fisherman who use stun to look for fish. The object of this research is the culture of Electric shock activity in maintaining the local economy RT 01 Mendawai Seberang Pangkalan Bun. The techniques used in data collection are observation, interview and documentation. In the technical validity of the data, the researcher was used a triangulation process.             The results from the culture of electric shockonmaintaining economic society at the RT. 01 Mendawai Seberang Pangkalan Bunis an activity that has long been done and the result of cultural transformation that has been handed ancestors.This activity is one way to sustain the local economy of the challenges existing conditions. Using a stun for fishing has several factors because it is easy, effective and efficient.Economicnecessity, the capital required is not too large, another effort is difficult to do, and the domicile is the reason behind this culture is still being conducted until today. The impact of electric shock toward the ecosystem of fish just a little bit because it is not spent the ecosystem of fish. Only a small portion is taken for the purposes of trade. Whereas the impact on the fishermanthemselves the possibility exists, if its application is not appropriate and not in accordance with the existing procedures could harm the fishermanthemselves.